Food And Beverage Management Purchase Kartika One Hotel - Setiawan, Rifky; Nugraha, Rizki Nurul; Mulya, Muhammad Hafiz; Adilla, Rosa; R, Amanda M F (Peneliti.net, 2023)
This research draws on the results of industrial field observations regarding the procurement of goods at the Kartika Hotel. This research discusses Food and Beverage at the hotel. This type of research uses a descriptive method with a qualitative approach. Data obtained from interviews and documentation with the purchasing department This journal aims to identify how the implementation of Purchasing F&B section management is very important to be applied in the hospitality industry and then assist by using the SWOC method (Strengths, Weaknesses, Opportunities, and Challenges). Through this case study, the author analyzes the identification of the purchasing management of the F&B section, the implementation of the implementation strategy, and the purpose of implementing purchasing. The results of this study conclude that controlling the supply of goods is very important for hotel needs in the contract strategy with suppliers, procurement of superior goods, and management carried out by purchasing management in maintaining its excellence.